Making Male Privilege Visible - Hoffmann, René (TRAILS: Teaching Resources and Innovations Library for Sociology, 2014)
Privileges are unearned advantages or benefits people receive because of their group memberships. There are two important features that work in concert to make our privileges invisible: (1) the characteristics of the privileged group become cultural norms and (2) members of the privileged class can choose to ignore or acknowledge oppression. This exercise is designed to make male privileges explicit to students of all genders. Because systemic male privilege masks itself as being a neutral facet of society, the exercise not only demonstrates the existence of male privileges to male students, but also helps members of the oppressed group articulate some of the inequality they experience, which is often unacknowledged by wider society.